Abnormal functional connectivity between ipsilesional V5/MT+ and contralesional striate cortex (V1) in blindsight - Silvanto, Juha; Walsh, Vincent; Cowey, Alan (Experimental brain research, 2009)
Damage to the visual cortex can lead to changes in anatomical connectivity between the remaining areas. For example, after a unilateral lesion to striate cortex (V1), an abnormal anatomical pathway can develop between the lateral geniculate nucleus of the undamaged hemisphere and the motion area V5/MT+ in the damaged hemisphere, accompanied by a hypernormal callosal connection between the area V5/MT+ of the two hemispheres. Here we investigated, using transcranial magnetic stimulation (TMS), the functional significance of these pathways in the blindsight subject GY, in whom they were first demonstrated. We show that TMS applied over the extrastriate area V5/MT+ in GY's damaged hemisphere modulates the appearance of phosphenes induced from V1 in the normal hemisphere. In contrast, in neurologically normal control subjects, TMS applied over V5/MT+ never influenced the phosphenes induced from V1 in the other hemisphere. The findings indicate an abnormal functional connectivity between V5/MT in the damaged hemisphere and the early visual cortex in the normal hemisphere, consistent with GY's abnormal anatomical connectivity.